Memaknai Belajar di Sekolah Kehidupan Agar Lulus Menghadapi Masalah di Universitas Kehidupan - Dedi Saputra (Jurnal Edukasi, 2022)
Learning is often associated with the process of acquiring knowledge, which is carried out through formal institutions such as schools and universities. In fact, broadly speaking, learning is a process that every individual always goes through throughout their life. So it can be interpreted that learning always follows a person as long as that individual is still alive. So it is very appropriate that the term long-lived education is a great concept for living life. In line with the concept of learning, of course, it is also related to problems in life that will always exist as long as a person is still alive. This means that no one lives without problems, big or small; there are still problems that must be resolved. Then a person learns from life's problems. Learning and problems are essentially life itself. Learning from problems or learning to solve problems will always be present in human life (University of Life).